The Role of Chemistry in Achieving Sustainable Development Goals: Green Chemistry Perspective - (:unkn) unknown (My University, 2025)
Green chemistry, also referred to as sustainable chemistry, has emerged as a crucial framework for addressing global sustainability challenges and advancing the United Nations 2030 Sustainable Development Goals (UN-SDGs). By focusing on designing chemical products and processes that minimize hazardous substances, green chemistry reduces environmental pollution, conserves resources, and improves public health. It promotes safer, more efficient chemical processes aligned with sustainability principles. The twelve principles of green chemistry offer actionable strategies for achieving key SDGs. For example, green chemistry ensures clean water and sanitation (SDG 6) by minimizing toxic chemical releases into water systems and addresses climate action (SDG 13) through low-carbon technologies and sustainable energy sources. It supports responsible production and consumption (SDG 12) by advancing circular economy practices and fostering sustainable industrial processes. In Africa, green chemistry is drawing attention, demonstrating significant contributions to sustainable development. Conferences in Africa have fostered collaboration among researchers, policymakers, and industry leaders while African countries continue to adopt green technologies, including cleaner production techniques and renewable feedstocks in chemical manufacturing. Research laboratories across the continent are implementing techniques like solvent-free synthesis and bio-based catalysts, reducing environmental impacts and enhancing resource efficiency. This article highlights how green chemistry principles drive progress toward the UN-SDGs in Africa. By integrating these principles, green chemistry can help create a sustainable global economy, advancing environmental stewardship, social well-being, and economic growth.
Keywords: African Research